Quality assessment for three common conditions in primary care: validity and reliability of review criteria developed by expert panels for angina, asthma and type 2 diabetes. Issue 2 (1st June 2002) - Campbell, S M; Hann, M; Hacker, J; Durie, A; Thapar, A; Roland, M O
Abstract : Objectives: To field test the reliability, validity, and acceptability of review criteria for angina, asthma, and type 2 diabetes which had been developed by expert panels using a systematic process to combine evidence with expert opinion. Design: Statistical analysis of data derived from a clinical audit, and postal questionnaire and semi-structured interviews with general practitioners and practice nurses in a representative sample of general practices in England. Setting: 60 general practices in England. Main outcome measures: Clinical audit results for angina, asthma, and type 2 diabetes. General practitioner and practice nurse validity ratings from the postal questionnaire. Results: 54%, 59%, and 70% of relevant criteria rated valid by the expert panels for angina, asthma, and type 2 diabetes, respectively, were found to be usable, valid, reliable, and acceptable for assessing quality of care. General practitioners and practice nurses agreed with panellists that these criteria were valid but not that they should always be recorded in the medical record. Conclusion: Quality measures derived using expert panels need field testing before they can be considered valid, reliable, and acceptable for use in quality assessment. These findings provide additional evidence that the RAND panel method develops valid and reliable review criteria for assessing clinical quality of care.